2016
DOI: 10.1037/men0000014
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about and attitudes toward vasectomy in Mexico: Relationships with gender roles, ambivalent sexism, and demographic variables.

Abstract: Vasectomy is a contraceptive method safer, less invasive, and easier to practice than bilateral tubal ligation. However, it is less commonly used especially in developing countries like Mexico. In the present study, we sought to determine whether some demographic and gender ideology variables are related to beliefs and attitudes toward vasectomy. Three hundred eighty-nine Mexican adults were surveyed; neither male participants nor the partners of female participants had had a vasectomy. We examined participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
3
0
2
Order By: Relevance
“…The results of the present study indicate that views of vasectomy among men with a limited educational level are more negative in tone than those of men with a higher education. This finding is consistent with a previous study conducted with Mexican men and women which identified that participants with the highest educational level were the most likely to acknowledge the benefits of vasectomy (Hernández-Aguilera & Marván, 2016). Moreover, Mexican men with higher education and income have a greater prevalence of vasectomy than those less educated (Lara-Ricalde et al, 2010; Oliva Malagón et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study indicate that views of vasectomy among men with a limited educational level are more negative in tone than those of men with a higher education. This finding is consistent with a previous study conducted with Mexican men and women which identified that participants with the highest educational level were the most likely to acknowledge the benefits of vasectomy (Hernández-Aguilera & Marván, 2016). Moreover, Mexican men with higher education and income have a greater prevalence of vasectomy than those less educated (Lara-Ricalde et al, 2010; Oliva Malagón et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…We assessed attitudes toward vasectomy using 33 items thought to impact the perceived acceptability of having a vasectomy. Items were developed by the authors or based on work by Hernandez-Aguilera and Marván (2015 , 2016 ). All attitude questions used a 5-point Likert scale ranging from strongly disagree to strongly agree .…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire measured men's vasectomy knowledge, attitudes, and information-seeking behaviors. The questionnaire was informed by a literature review, which revealed no known survey of these constructs in the United States, although related work was recently conducted in Mexico (Hernandez-Aguilera & Marván, 2015, 2016. Drawing on this research in Mexico, information gathered from the literature, and consultations with the coauthors, the first author developed a questionnaire consisting of items querying vasectomy knowledge, attitudes, and information seeking, as well as demographic information.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…Alcanzó el total de hijos planeados 95% 67% 9,2 2,3-36,7 0,000 Pensó operarse desde el primer hijo 17% 2% 9,1 1,1-73,7 0,014 Pensó operarse hasta después del total deseado 17% 2% 9,1 1,1-73,7 0,014 que lleva a los varones considerar la vasectomía. La escolaridad baja en este estudio duplico el riesgo de someterse al método; pues este tipo de escolaridad predomino en el grupo A y B; resultados alejados a los de Hernandez y Marvan 19 en donde la escolaridad baja se asocia a rechazo por el método anticonceptivo. El contar con tres o menos parejas sexuales es algo de importancia a destacar; pues más allá de este número de parejas se obtuvo un factor protector y no de riesgo.…”
Section: Usted… Casos Controles Rm Ic 95% Punclassified
“…Pareciera que aquellas creencias donde la impotencia sexual o disminución de la libido post-vasectomía predominaban en gran parte de la población poco a poco están siendo desplazadas, en nuestro estudio solo 3% de los casos persiste con esta ideología; aunque se debe tomar en consideración la zona urbana y con acceso a la información que tiene la unidad de medicina familiar. Resultado similar a Fernández Aragón y cols 19 . Más de la población estudiada piensa que familiares o amigos opinarían si optan por la vasectomía; corroborando que es una parte importante para el hombre la opinión de los demás; resultados parecidos a los de García Franco y cols 1 .…”
Section: Opiniones Acerca De La Vasectomía Y Los Operados %Casos %Controles Punclassified